Strategies to manage bullying in semi-public schools in the Potgietersrus Circuit, Waterberg District of Limpopo Province - Mashishi, Mmaphuti Flora (My University, 2020)
Bullying is a major challenge that affects learners in schools world-wide. Negative effects of bullying on learners are physical and psychological including depression, anxiety and school declining performances. Every learner is entitled to a safe school environment without being a victim or a bystander of bullying. Therefore the main objective was to explore strategies that could be implemented to manage bullying in schools. A qualitative approach with a case study was used to provide an understanding of the phenomenon of bullying and how it could be managed. The grade three and six learners of two former model-c schools in Potgietersrus circuit in Limpopo Province were purposively selected as participants with the aim of representing learners in the junior and intermediate phase. Observation, interviews and document analysis were used as data collection methods. The data collected was developed through thematic content data. The results indicated that bullying is receiving increasing attention with appropriate responsiveness and effective management strategies. Additional measures that can help reduce the prevalence of bullying and impact were explored and included bullying intervention strategies, increased playground supervision, behaviour modification strategies, encouraging learners to report bullying incidents and the adoption of School Based Support Team to assist in combating bullying. It is recommended that the department of education, educators and learners can adopt the explored strategies as part of intervention process to combat bullying in the school environment and to ensure that schools are still seen as safe places for all learners
Thesis (M. Ed.) -- University of Limpopo, 2020
Keywords: Bullying in schools; Learners; Management strategies; Bullying in schools -- Prevention; Bullying in schools -- Prevention